(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Urbanization has brought in its wave a host of problems particularly for the government of the developing countries. Although, higher income is an added benefits to the urban dwellers, yet urban poverty and unemployment and a host of problems associated with pollution and congestation are the most noted indicators of urban failures.The present study emphasis on the current situation of urban Alwar.With new phase comes new challenges .Urbansization has its side effects in a way when planning doesnot meet the implementation on ground level just like “A vehicle without fuel is just nothing irrespective of the fact how grand it is”.The study deals with the changing phase of Alwar,Alwar being Urban itself is a challenge and the need for implementation of proper planning done by management.